2023
DOI: 10.3389/fonc.2023.1132141
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of traditional Chinese medicine as sensitizer in reversing chemoresistance of colorectal cancer

Abstract: In recent years, the incidences and mortalities from colorectal cancer (CRC) have been increasing; therefore, there is an urgent need to discover newer drugs that enhance drug sensitivity and reverse drug tolerance in CRC treatment. With this view, the current study focuses on understanding the mechanism of CRC chemoresistance to the drug as well as exploring the potential of different traditional Chinese medicine (TCM) in restoring the sensitivity of CRC to chemotherapeutic drugs. Moreover, the mechanism invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 216 publications
0
5
0
Order By: Relevance
“…22 Additionally, as highlighted in studies like those by Lin et al, the varied methodologies and populations across studies may affect the generalizability of our findings. 23 In conclusion, our meta-analysis provides encouraging evidence for the use of Jie Geng and Huang Qi in reducing PWIs and enhancing recovery in colorectal cancer surgeries. These findings suggest the potential of TCM as a valuable adjunct in postoperative care, echoing the sentiments of studies like those by Gao et al Future research should not only focus on conducting highquality RCTs but also delve into the pharmacological interactions and safety profiles of TCM, as suggested by recent studies.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…22 Additionally, as highlighted in studies like those by Lin et al, the varied methodologies and populations across studies may affect the generalizability of our findings. 23 In conclusion, our meta-analysis provides encouraging evidence for the use of Jie Geng and Huang Qi in reducing PWIs and enhancing recovery in colorectal cancer surgeries. These findings suggest the potential of TCM as a valuable adjunct in postoperative care, echoing the sentiments of studies like those by Gao et al Future research should not only focus on conducting highquality RCTs but also delve into the pharmacological interactions and safety profiles of TCM, as suggested by recent studies.…”
Section: Discussionmentioning
confidence: 69%
“…The quality assessment revealed that the majority of the studies included were of suboptimal quality, a concern also raised in other systematic reviews within the field 22 . Additionally, as highlighted in studies like those by Lin et al, the varied methodologies and populations across studies may affect the generalizability of our findings 23 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Traditional Chinese medicine's characteristics encompass many ingredients, targets, and synergistic effects. Inducing cell apoptosis and autophagy, inhibiting tumor cell proliferation, suppressing epithelial-mesenchymal transition and angiogenesis, modulating chemotherapy resistance, tumor metabolism, and tumor immune regulation may treat colorectal cancer (54)(55)(56). In contrast to the adverse effects associated with chemotherapy drugs, including bone marrow suppression, reduced blood cell count, gastrointestinal reactions, liver function impairment, and alopecia, the use of traditional Chinese medicine for treating colorectal cancer exhibits a lower incidence of side effects and drug resistance (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…However, issues concerning their bioavailability and toxicity have impeded their clinical application. By encapsulating TCMs, nanocarriers, such as liposomes, polymeric nanoparticles, and organic nanoparticles, can shield them from decomposition in the biological milieu [ 253 ]. In addition, they can increase the solubility and stability of TCMs, resulting in greater absorption and bioavailability.…”
Section: Materials-based Nanocarriers In Delivery Of Active Ingredien...mentioning
confidence: 99%